Study on the multi-parameter combination analysis and quantitative evaluation of the efficacy of extracorporeal shock wave therapy for plantar fasciitis - Zhao, Jing; Du, Yongfei; Xiang, Zhijie; Tan, YuZhe; Hu, Jiayue; Yang, Liu; Wei, Haicheng (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundExtracorporeal shock wave therapy (ESWT) is an effective non-invasive treatment for plantar fasciitis (PF) that relieves chronic pain, promotes tissue healing, and improves function, and is particularly suitable for cases unresponsive to conservative management. Compared with surgery, ESWT is less invasive, more cost-effective, and has demonstrated favorable long-term outcomes.Aim of the studyTo address the limited reliability of subjective scales and the clinical translation difficulties of laboratory gait analysis in current efficacy evaluation of ESWT for PF, we propose a monocular-vision, multi-parameter combination framework for multidimensional decoupling assessment of gait dynamics.MethodsUsing a monocular RGB camera, we recorded a total of 633 gait videos from 23 PF patients before and after ESWT intervention. Lower-limb kinematic parameters were extracted with the CtransPose pose-estimation algorithm and dimensionality reduction and reconstruction were performed by principal component analysis (PCA). Five core functional dimensions explaining a cumulative variance of 89.18% were successfully extracted, and a theoretical framework for multidimensional coupling of gait features was established.ResultsThe primary efficacy dimension (PC1) improved significantly after treatment: step length increased from 0.33 [0.30, 0.39] m to 0.37 [0.29, 0.44] m, stride length increased from 0.59 [0.52, 0.69] m to 0.63 [0.55, 0.75] m, and walking speed increased from 0.59 [0.48, 0.67] m/s to 0.62 [0.55, 0.75] m/s (all P < 0.05). The coordinated improvement of these objective parameters suggests that ESWT may effectively restore basic propulsion-phase locomotor function by alleviating pain. The gait-optimization dimension (PC3) reflected a pattern of improved gait efficiency, characterized by significantly increased walking speed (P < 0.001) while cadence remained unchanged, reflecting release of pain-avoidance strategies. The swing-control dimension (PC5) showed a significant reduction in maximum swing angle (P = 0.003), indicating a favorable transformation in swing control mechanisms.ConclusionBy establishing an objective assessment method centered on PC1 with PC3 and PC5 as sensitive indicators, this study provides a new paradigm for quantitative ESWT efficacy evaluation and individualized rehabilitation planning.